``Is That What It Means?'' Performative Storytelling in Early Childhood Education: Meaning-making Through Interaction - Pradina, Fathia Anggriani; Yuwono, Untung; Kushartanti, Bernadette (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
Early childhood education is inextricably linked to the role of adults in every aspect of its process. In addition to formal classroom learning, storytelling with a storyteller is another activity that involves adults. The dialogic interaction between storyteller and children fosters the creation of meaning. This study examines how storytelling, as an interactional practice, can dynamically construct meaning together between storyteller and children. Sixty-one kindergarten children participated in this study during a one and half hour storytelling activity. The qualitative and interactional approach used in this study focused on moment-to-moment exchanges during the naturally occurring storytelling event. The findings indicate that meaning-making occurs through three interactional patterns: eliciting children's interpretations, shaping meaning through performative gestures, and aligning individual interpretations into a shared understanding. These patterns demonstrate how children's responses gradually emerge, are guided, and coordinated in the interaction. The storyteller plays a central role in orchestrating participation and directing interpretation through performative and multimodal resources, rather than through explicit instruction. The study proposes that performative storytelling constitutes a dialogic space for early literacy, where children engage with narrative through active participation and collaborative meaning-making.